Diet fuelling inflammatory bowel diseases: preclinical and clinical concepts. Issue 12 (16th September 2022) - Adolph, Timon E; Zhang, Jingwan
Abstract : The diet and gut microbiota have been extensively interrogated as a fuel for gut inflammation in inflammatory bowel diseases (IBDs) in the last few years. Here, we review how specific nutrients, typically enriched in a Western diet, instigate or deteriorate experimental gut inflammation in a genetically susceptible host and we discuss microbiota-dependent and independent mechanisms. We depict the study landscape of nutritional trials in paediatric and adult IBD and delineate common grounds for dietary advice. Conclusively, the diet reflects a critical rheostat of microbial dysbiosis and gut inflammation in IBD. Dietary restriction by exclusive enteral nutrition, with or without a specific exclusion diet, is effectively treating paediatric Crohn's disease, while adult IBD trials are less conclusive. Insights into molecular mechanisms of nutritional therapy will change the perception of IBD and will allow us to enter the era of precision nutrition. To achieve this, we discuss the need for carefully designed nutritional trials with scientific rigour comparable to medical trials, which also requires action from stake holders. Establishing evidence-based dietary therapy for IBD does not only hold promise to avoid long-term immunosuppression, but to provide a widely accessible therapy at low cost. Identification of dietary culprits disturbing gut health also bears the potential to prevent IBD and allows informed decision making in food politics.